Nursing Cultural Competence Scale (NCCS): validity & reliability - Juhdeliena Juhdeliena; Agustina Saputri; Eva Chris Veronica Gultom (Jurnal Keperawatan)
Introduction: Cultural competence is an important aspect for nurses to be able to provide culturally sensitive care in diverse healthcare environments. However, there are few tools that can measure this competence in the Indonesian context. Objectives: This study aimed to evaluate the content validity and reliability of the Nursing Cultural Competence Scale (NCCS) questionnaire adapted for nurses in Indonesia. Methods: This study used a cross-sectional design involving 30 nurses in hospitals in Indonesia. Furthermore, the relevance of the questionnaire items was assessed. Content Validity Index (CVI) was conducted on each questionnaire item with a focus on relevance, clarity, simplicity and ambiguity. Results: Item-CVI (I-CVI) values ranged from 0.6 to 1, with an average I-CVI value of 0.99 for relevance, and 1.0 for ambiguity, simplicity, and clarity. Scale-CVI (S-CVI/UA) showed 97.6% agreement, indicating high item relevance, while S-CVI/Ave exceeded 0.99. Cronbach's alpha was 0.963, indicating excellent reliability. Conclusions: The high CVI and Cronbach's alpha values mean that the Indonesian NCCS is a valid and reliable tool to assess nurses' cultural competence. However, future research could address test-retest reliability and involve a larger panel of experts with diverse backgrounds to strengthen content validity. This instrument can help nurses in Indonesia to assess their cultural competence in providing health services. The conclusion of this study shows that the NCCS questionnaire in the Indonesian context has high content validity and is therefore reliable for assessing cultural competence in nurses.